2022
DOI: 10.1038/s41598-022-25911-x
|View full text |Cite
|
Sign up to set email alerts
|

Antarctic fungi with antibiotic potential isolated from Fort William Point, Antarctica

Abstract: The Antarctic continent is one of the most inhospitable places on earth, where living creatures, mostly represented by microorganisms, have specific physiological characteristics that allow them to adapt to the extreme environmental conditions. These physiological adaptations can result in the production of unique secondary metabolites with potential biotechnological applications. The current study presents a genetic and antibacterial characterization of four Antarctic fungi isolated from soil samples collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 108 publications
0
2
0
Order By: Relevance
“…The new metabolites could be much needed antibiotics to combat drug resistance. Related to this possibility, four fungi were isolated from the region by Ordóñez-Enireb et al 9 which were identified as Antarctomyces sp., Thelebolus sp., Penicillium sp., and Cryptococcus gilvescens. They were shown to have varying degrees of antibacterial activity and indicate clearly the need to preserve the Antarctic as a potential source of useful fungi.…”
Section: The Collectionmentioning
confidence: 99%
“…The new metabolites could be much needed antibiotics to combat drug resistance. Related to this possibility, four fungi were isolated from the region by Ordóñez-Enireb et al 9 which were identified as Antarctomyces sp., Thelebolus sp., Penicillium sp., and Cryptococcus gilvescens. They were shown to have varying degrees of antibacterial activity and indicate clearly the need to preserve the Antarctic as a potential source of useful fungi.…”
Section: The Collectionmentioning
confidence: 99%
“…Cold-adapted microorganisms possess a variety of mechanisms to maintain vital cellular functions at low temperatures, such as cold-active extracellular enzyme production, synthesis of antifreeze protein, elevated unsaturated fatty acids, an increase of pigmentation, resistance to osmotic stress, etc. [ 9 , 10 ]. Cold-active enzymes can catalyze different reactions at low temperatures because of their high specific activity and capability to support transcription and translation at low temperatures [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%